Prevention of waste from unsolicited mail in households: measuring the effect of anti-advertising stickers in Barcelona - Ignasi Puig-Ventosa; Marta Jofra-Sora; Jaume Freire-González (Journal of Material Cycles and Waste Management, 2014)
Unsolicited mail (also called junk mail) received by households is a potential source for the application of waste prevention measures. There are insufficient systematic studies on the potential reduction of this kind of waste and on the effects of certain policies for its reduction. The present research presents the results of an assessment of the effectiveness of anti-advertisement stickers in Barcelona, as a way of preventing waste generation. 50 households from 25 buildings were monitored during a period of 3 months. The retrieved advertising material was weighted and classified into addressed and unaddressed material, and into several categories of the activities being advertised. The number of units of advertising material was also calculated. The statistical analysis (which includes a pairwise analysis within buildings in order to isolate the effect of the sticker) concludes that the use of stickers could prevent between 0.31 and 0.36 kg/inhabitant/year, which represents around 43 % of all unsolicited advertising and 0.4 % of all paper waste generated in Barcelona.
Keywords: 330